Laser Ignition of Ammonium Perchlorate/Aluminum Composition Confined into PMMA Capsule. Issue 3 (27th January 2022) - Tsipilev, Vladimir; Forat, Egor; Medvedev, Valerii; Yakovlev, Aleksey; Vavilov, Vladimir; Shiryaev, Vladimir
Abstract: A two‐component composition of ammonium perchlorate and nanosized aluminum powder can be ignited by millisecond Nd laser radiation. However, the mixture exposed to laser radiation pulse through polymethyl methacrylate (PMMA) capsule demonstrates less sensitivity when compared to ignition of the uncovered sample. Such behavior is uncommon to gasified energetic materials. It is shown that the sensitivity of uncovered samples does not change if the surrounding atmosphere is changed from air to argon. It was found that the cover of PMMA decreases the sensitivity of the mixture due to heat dissipation from the ignition zone, thereby reducing its reactivity. Abstract :